Abordagem dos maus tratos na infância por unidades de saúde da família - Lelis, Laura Garcia Leal [UNESP] (Universidade Estadual Paulista (Unesp), 2010)
The goal of this study was to apprehend conceptualizations and professional experiences concerning child maltreatment as reported by physicians and nurses working for the Family Health Strategy implemented in a medium-sized city in São Paulo state. It is a descriptive qualitative study in which 20 professionals were included and semi-structured taped interviews were used. The data obtained were analyzed according to the Collective Subject Discourse and systematized into five themes: Conceptualizations of child maltreatment; Professional training to work in this field; Professional experiences related to such aggravations; Difficult and easy aspects faced during care provision to child maltreatment in the Family Health Strategy; Proposals to promote child safety. It was concluded that care provision to such aggravation types by family health units is configured as an important strategy to promote child safety and support families in relation to this issue. However, it was observed that, in order to qualify professionals for such care provision, it is necessary to invest in continuing education for the multiprofessional team. Also, municipal policies concerning care provision to child abuse, particularly in the organization of integrated work of the health care, education, social welfare and justice sectors must be urgently established by actively including the general society in such process

O objetivo geral desse estudo foi apreender as concepções e experiências profissionais quanto aos maus tratos contra criança, a partir de médicos e enfermeiros atuantes na Estratégia Saúde da Família implementada em município de médio porte do interior paulista. Trata-se de estudo descritivo qualitativo que abordou 20 profissionais, por meio de entrevistas semiestruturadas gravadas. Os dados obtidos foram analisados segundo o Método do Discurso do Sujeito Coletivo, sendo sistematizados em cinco temas: Concepções sobre maus tratos na infância; Preparo profissional para atuação nessa área; Experiências profissionais quanto a esses agravos; Dificuldades e facilidades na atenção aos maus tratos na infância na Estratégia Saúde da Família; Propostas para promover a segurança na infância. Conclui-se que a atenção a esses tipos de agravos pelas unidades de saúde família configura-se como importante estratégia para promover a segurança da criança e apoiar a família, neste sentido. Entretanto, verifica-se que para a qualificação dessa atenção, há a necessidade de se investir na educação permanente da equipe multiprofissional. Também, urge efetivar a política municipal de atenção à violência na infância, especialmente na organização do trabalho integrado dos setores da saúde, educação, assistência social e justiça, incluindo ativamente a sociedade em geral, nesse processo
Keywords: Enfermagem pediatrica; Crianças – Maus-tratos; Família